ANALISIS KELAYAKAN USAHA AGROINDUSTRI MIE SAGU DI KECAMATAN TEBING TINGGI KABUPATEN KEPULAUAN MERANTI - Tri Mukti; Septina Elida (UIR Press, 2017)
Sago is the potential agricultural product in Kapulauan Meranti Regency and can be processed into various food product, including sago noodles. This study aims to find the sago noodles business profile, feasibility level viewed from financial and non financial aspect the sago noodles agroindustry in Tebing Tinggi District Kepulauan Meranti Regency. This research used survey method. Data were analyzed descriptively qualitative and quantitative. The non-financial aspects of the study consist of market, technical and legal aspects, while the financial aspects are analyzed by investment criteria. The results showed that sago noodles agroindustry entrepreneur including productive age with the average age of 46 years, education is still low that is 9 years (SMP) and experienced in trying sago noodle processing that is for 16 years. Sago noodle business is included in small-scale business and home industrial, processing of sago noodles using semi-modern and traditional technology. Non-financial feasibility of sago noodles on the market aspect and technical aspects is feasible to cultivate but the legal aspect is not yet feasible. Finally, sago noodles are feasible to be cultivated because they meet the investment feasibility criteria, with NPV value Rp 444,589,796,57, Net B / C 1,32, IRR 47%, PB (payback period) 2 years 2 months. Based on switching value analysis, the business of sago noodle agroindustry is more sensitive to the 10% output price decrease compared to 10% input price increase.